2021
DOI: 10.1590/s1413-415220190087
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização hidrogeoquímica de águas subterrâneas utilizadas para abastecimento público na porção nordeste do Sistema Aquífero Guarani

Abstract: RESUMO O Sistema Aquífero Guarani (SAG) compreende um dos mais importantes aquíferos do mundo, tanto pela grande reserva quanto pela qualidade de suas águas subterrâneas. Entretanto, nem todas as regiões, nas quais o SAG é utilizado no abastecimento público, possuem estudos a respeito do quimismo de suas águas e de sua associação com a geologia. Este trabalho apresenta a caracterização hidrogeoquímica das águas subterrâneas do SAG utilizadas no abastecimento público em São Carlos, São Paulo, região nordeste do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…The use of nonparametric tests, such as those used in this study, to assess the assumptions of sample distribution of data is something quite consolidated in the literature and several authors have used these tests in studies related to water quality. Furthermore, the KS and SW normality tests are applied in several studies regarding surface or groundwater quality (e.g., Santos et al, 2020;Batista et al, 2021;Leite et al, 2021;Valentini et al, 2021c;Valentini et al, 2021d;Silveira et al, 2021). Santos et al (2021), for example, applied KS and SW tests for evaluate data sampling distribution of in order to know which correlation coefficient would be more appropriate for application of correlation analysis between these data and Water Quality Index calculated in their study.…”
Section: Resultsmentioning
confidence: 99%
“…The use of nonparametric tests, such as those used in this study, to assess the assumptions of sample distribution of data is something quite consolidated in the literature and several authors have used these tests in studies related to water quality. Furthermore, the KS and SW normality tests are applied in several studies regarding surface or groundwater quality (e.g., Santos et al, 2020;Batista et al, 2021;Leite et al, 2021;Valentini et al, 2021c;Valentini et al, 2021d;Silveira et al, 2021). Santos et al (2021), for example, applied KS and SW tests for evaluate data sampling distribution of in order to know which correlation coefficient would be more appropriate for application of correlation analysis between these data and Water Quality Index calculated in their study.…”
Section: Resultsmentioning
confidence: 99%
“…(ZHANG, et al 2022); as well as the water crisis caused by climate change at the expense of anthropic activities. Life on the planet consists of a substantial portion of water, a chemical compound formed from two hydrogen atoms and an oxygen atom (LEITE, et al [11,12]);reported in their study when they cite the 2030 agenda in its Sustainable Development Goals (SDGs) 06 and 14, water is a necessary asset for everyone and needs to be conserved, and environmental preservation is one of the factors for maintaining its renewal cycle.…”
Section: Structure and Social Policiesmentioning
confidence: 99%
“…A comprehensive survey of the study area was conducted, accompanied by an inventory of water points. A total of 10 groundwater points and 5 surface water points were strategically selected for further analysis based on criteria such as spatial representativeness, accessibility, availability of infrastructure, and cooperation of operators and owners [38]. Georeferencing was performed for all fifteen points, and a detailed map was generated using ArcGIS 11.0 software as presented in Figure 4.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%